Hydrogen gas sensor based on mesoporous In2O3 with fast response/recovery and ppb level detection limit. (13th December 2018) - Li, Zhijie; Yan, Shengnan; Wu, Zhonglin; Li, Hao; Wang, Junqiang; Shen, Wenzhong; Wang, Zhiguo; Fu, YongQing
Abstract: Hydrogen gas sensors were fabricated using mesoporous In2 O3 synthesized using hydrothermal reaction and calcination processes. Their best performance for the hydrogen detection was found at a working temperature of 260 °C with a high response of 18.0 toward 500 ppm hydrogen, fast response/recovery times (e.g. 1.7 s/1.5 s for 500 ppm hydrogen), and a low detection limit down to 10 ppb. Using air as the carrier gas, the mesoporous In2 O3 sensors exhibited good reversibility and repeatability towards hydrogen gas. They also showed a good selectivity for hydrogen compared to other commonly investigated gases including NH3, CO, ethyl alcohol, ethyl acetate, styrene, CH2 Cl2 and formaldehyde. In addition, the sensors showed good long-term stability. The good sensing performance of these hydrogen sensors is attributed to the formation of mesoporous structures, large specific surface areas and numerous chemisorbed oxygen ions on the surfaces of the mesoporous In2 O3 . Highlights: Hydrogen gas sensor was fabricated using mesoporous In2 O3 . The hydrogen gas sensor exhibited fast response/recovery times. The hydrogen gas sensor had very low detection limit of 10 ppb. The hydrogen gas sensor showed high responses and good long-term stability.